Secure Smart Green House Farming using Blockchain Technology - et al., P.Chinnasamy (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The evolving agricultural technologies used mostly for remote access and modernization in farming connected via the Internet of Things (IoT) have been grown rapidly. However because of the wide size of all its broadcaster's propagandizing existence, it has some significant concerns with respect to security and privacy. We utilize blockchain to address such security breaches, allowing the development of a decentralized distributed blockchain system that's also exchanged between the IoT cluster heads. This article's major focus is provide smart greenhouse farmlands with a portable blockchain-based infrastructure which offers integrity and confidentiality. Where, green-house IoT sensor nodes are function as a blockchain centrally controlled to optimize the energy consumption by utilizing secure immutable ledgers. Furthermore, we present a significant solution that integrates blockchain technology via IoT devices to offer Smart Greenhouse cultivation with an enhanced secure communication.